2023
DOI: 10.3390/ijms24076364
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Berberine Thermosensitive Hydrogel in Periodontitis via PI3K/AKT Pathway In Vitro

Abstract: Periodontitis is a long-term inflammatory illness and a leading contributor to tooth loss in humans. Due to the influence of the anatomic parameters of teeth, such as root bifurcation lesions and the depth of the periodontal pocket, basic periodontal treatment on its own often does not completely obliterate flora microorganisms. As a consequence, topical medication has become a significant supplement in the treatment of chronic periodontitis. Berberine (BBR) has various pharmacological effects, such as hypogly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Some scholars have shown that the strips could be used to polish the surfaces of adjacent fillings, and the surface roughness and patient comfort would significantly improve (Ozdemir et al, 2022). (Wang et al, 2023). Therefore, it would be more suitable in clinical practice to limit the range of tooth surface detection from 5 mm in the crown to 5 mm in the root with the cemento-enamel junction as the midline, which has a certain reference value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars have shown that the strips could be used to polish the surfaces of adjacent fillings, and the surface roughness and patient comfort would significantly improve (Ozdemir et al, 2022). (Wang et al, 2023). Therefore, it would be more suitable in clinical practice to limit the range of tooth surface detection from 5 mm in the crown to 5 mm in the root with the cemento-enamel junction as the midline, which has a certain reference value.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the existence of root furcation in premolars and molars, basic treatment and polishing are insufficient once the furcation area is pathologically involved. Therefore, the average height of the root bifurcation limits the scope of periodontal treatment and polishing (Wang et al, 2023 ). Therefore, it would be more suitable in clinical practice to limit the range of tooth surface detection from 5 mm in the crown to 5 mm in the root with the cemento–enamel junction as the midline, which has a certain reference value.…”
Section: Discussionmentioning
confidence: 99%
“…Thermosensitive hydrogels, for example, are in liquid form at low temperatures but gelate at higher temperatures, a property crucial for effective drug delivery. Wang et al (2023) developed a berberine heat-sensitive hydrogel that gels rapidly at body temperature (37 °C) within approximately 3 min, demonstrating efficacy in treating periodontal inflammatory bone conditions by modulating the PI3K/AKT signaling pathway and offering anti-inflammatory and osteogenic benefits. Xu et al (2019) created an injectable thermosensitive hydrogel that continuously released aspirin and erythropoietin, facilitating the healing of inflammation and alveolar bone repair.…”
Section: Hydrogels As Drug Delivery Systemsmentioning
confidence: 99%
“…In addition, to enhance the bioactivity of hydrogel scaffolds, β-GP matrix temperature-sensitive hydrogels are often used in combination with chitosan [116]. Wang et al [117] used chitosan in combination with β-GP to prepare a temperature-sensitive hydrogel for the promotion of periodontitis repair and bone regeneration, and their research found that berberine thermosensitive hydrogel may be an effective treatment for periodontitis, which can exert anti-inflammatory and osteogenic effects through the PI3K/AKT signaling pathway. Lu et al [118] prepared a thermosensitive hybridized hydrogel scaffold using collagen I (Col-I) In a word, photocurable hydrogel may become an excellent scaffold for bone repair, but the demand for photoinitiators limits its application in some fields, and the selection of photoinitiators becomes a key factor in determining the polymerization efficiency and the required light wavelength.…”
Section: Temperature-sensitive Hydrogelsmentioning
confidence: 99%